Combination and QCD analysis of charm production cross section measurements in deep-inelastic ep scattering at HERA - Abramowicz, H; Abt, I; Adamczyk, L; Adamus, M; Aggarwal, R; Alexa, C; Andreev, V; Antonelli, S; Antonioli, P; Antonov, A; Arneodo, M; Arslan, O; et al. (2013)
Measurements of open charm production cross sections in deep-inelastic ep scattering at HERA from the H1 and ZEUS Collaborations are combined. Reduced cross sections σredcc̄ for charm production are obtained in the kinematic range of photon virtuality 2. 5≤Q2≤2000 GeV2 and Bjorken scaling variable 3{dot operator}10-5≤x≤5{dot operator}10-2. The combination method accounts for the correlations of the systematic uncertainties among the different data sets. The combined charm data together with the combined inclusive deep-inelastic scattering cross sections from HERA are used as input for a detailed NLO QCD analysis to study the influence of different heavy flavour schemes on the parton distribution functions. The optimal values of the charm mass as a parameter in these different schemes are obtained. The implications on the NLO predictions for W± and Z production cross sections at the LHC are investigated. Using the fixed flavour number scheme, the running mass of the charm quark is determined. © 2013 The Author(s).